Fluid jurisdictions colonial law and Arabs in Southeast Asia - Yahaya, Nurfadzilah, 1980- (Cornell University Press, 2020)
"Explores how the Arab diaspora's ambiguous embrace of European colonial authority in Southeast Asia extended colonial jurisdictions across the Indian Ocean from the late nineteenth century onwards"--